Simulation of the mixing bread dough process using computational techniques - Luchian, Mihaela; Stefanov, Stefan; Litovchenko, Igor; Mihaylov, Ivan; Hadzhіyskі, Vіlhelm (Simulation of the mixing bread dough process using computational techniques / M. I. Luchian, S. Stefanov, I. Litovchenko and other // Bulletin of the Transilvania University of Braşov. - 2016. - Vol. 6 (55), №. 2. - P. 129-134., 2013)
The process of dough mixing is a crucial operation in bakery industry to produce high-quality bread. Considered viscoelastic characteristics of dough, which are dependent on the moisture content and temperature. The purpose of this article is to develop advanced technology for modeling dough, which will provide a prediction of the optimal design parameters of the mixer.
Keywords: mixing; dough; modeling; computer; пермішування; тісто; моделювання; перемешивание; тесто; кафедра машин і апаратів харчових та фармацевтичних виробництв